Modelo espacial simples de uma economia com agentes: Uma proposta metodológica - Bernardo Alves Furtado; Isaque Daniel Eberhardt (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study simulates the evolution of artificial economies in order to understand the tax relevance of administrative boundaries in the quality of life of its citizens. The modeling involves the construction of a computational algorithm, which includes citizens, bounded into families; firms and governments; all of them interacting in markets for goods, labor and real estate. The real estate market allows families to move to households with higher quality or lower price when the families capitalize property values. The goods market allows consumers to search on a flexible number of firms choosing by price and proximity. The labor market entails a matching process between firms (given its location and offered wage) and candidates, according to their qualification. The government may mbe configured into a single region, or four or seven distinct sub-national governments, which are all economically conurbated. The role of government is to collect taxes on the value added of firms in its territory and transform the taxes into higher levels of quality of life for residents. As an illustration of the model the text suggests that the configuration of administrative boundaries is relevant to the levels of quality of life arising from the reversal of taxes. The model with seven regions is more dynamic, but more unequal and heterogeneous across regions. The simulation with only one region is more homogeneously poor. The study seeks to contribute to a theoretical and methodological framework and to describe, operationalize and test computer models of public finance analysis, with explicitly spatial and dynamic emphasis. Several alternatives of expansion of the model for future research are described.
Keywords: C63; H73; D01; 330; agent-based models; public finance; taxes; municipalities; limits; quality of life